Stellar Double Coronagraph: A Multistage Coronagraphic Platform at Palomar Observatory. (13th June 2016) - Bottom, Michael; Shelton, J. Chris; Wallace, James K.; Bartos, Randall; Kuhn, Jonas; Mawet, Dimitri; Mennesson, Bertrand; Burruss, Rick; Serabyn, Eugene
Abstract: We present a new instrument, the "Stellar Double Coronagraph, " a flexible coronagraphic platform. Designed for Palomar Observatory's 200″ Hale telescope, its two focal and pupil planes allow for a number of different observing configurations, including multiple vortex coronagraphs in series for improved contrast at small angles. We describe the motivation, design, observing modes, wavefront control approaches, data reduction pipeline, and early science results. We also discuss future directions for the instrument.